Exploring the role of inflammatory biomarkers in trigeminal neuralgia - Shenglong Lai; Haiyang Li; Yazhou Xing; Du Wu; Lin Wang; Qinghua Liang (Brain, Behavior, & Immunity - Health)
Background: Trigeminal neuralgia (TN) is a severe facial pain disorder with complex etiology. Inflammation has been suggested as a contributing factor to TN pathogenesis. This study investigates the causal relationship between inflammatory biomarkers, including 41 circulating inflammatory cytokines, C-reactive protein (CRP), and procalcitonin (PCT), and TN using Mendelian randomization (MR) analysis. Methods: A two-sample MR approach was employed using genome-wide association study (GWAS) data from 8293 Finnish individuals for inflammatory cytokines and data from the FinnGen database for TN. Instrumental variables (IVs) were selected based on genome-wide significance and clumping thresholds to avoid linkage disequilibrium. Inverse variance weighting (IVW) was used as the primary method, complemented by MR Egger regression, weighted median, simple mode, and weighted mode methods. Additionally, Bayesian Weighted MR (BWMR) and Multivariable MR (MVMR) were utilized to validate the findings and explore potential confounders. Results: The present MR analysis identified significant causal associations for three inflammatory cytokines with TN. Stem cell growth factor beta (SCGF-β) (OR = 1.362, 95% CI = 1.049–1.770, p = 0.021) and Interleukin-4 (IL-4) (OR = 1.533, 95% CI = 1.014–2.316, p = 0.043) were positively associated with TN, while Interleukin-16 (IL-16) (OR = 0.720, 95% CI = 0.563–0.921, p = 0.009) had a protective effect. CRP levels were also linked to TN risk (OR = 0.751, 95% CI = 0.593–0.951, p = 0.017). No significant causal effect of PCT on TN was observed. Sensitivity analyses confirmed the robustness of these findings, showing no evidence of horizontal pleiotropy or heterogeneity. Conclusion: This study highlights specific inflammatory biomarkers that may play pivotal roles in TN pathogenesis. SCGF-β and IL-4 are potential therapeutic targets due to their facilitative effects on TN, while IL-16 could offer protective benefits. CRP's association with TN further supports the involvement of systemic inflammation in this condition. These findings provide novel insights into TN's inflammatory mechanisms, suggesting new avenues for targeted interventions.